2011
DOI: 10.1007/s00018-011-0642-5
|View full text |Cite
|
Sign up to set email alerts
|

EP4 receptor stimulation down-regulates human eosinophil function

Abstract: Accumulation of eosinophils in tissue is a hallmark of allergic inflammation. Here we observed that a selective agonist of the PGE2 receptor EP4, ONO AE1-329, potently attenuated the chemotaxis of human peripheral blood eosinophils, upregulation of the adhesion molecule CD11b and the production of reactive oxygen species. These effects were accompanied by the inhibition of cytoskeletal rearrangement and Ca2+ mobilization. The involvement of the EP4 receptor was substantiated by a selective EP4 antagonist, whic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
52
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 47 publications
(57 citation statements)
references
References 62 publications
5
52
0
Order By: Relevance
“…This effect was at least partially reversed by the EP4 antagonist [18], although EP2 receptors were also found to be involved in this setup. In further experiments, we could substantiate the inhibitory role of EP4 receptors in eosinophils in assays of CD11b upregulation, production of reactive oxygen species and Ca 21 mobilization [40]. These findings have now fundamentally been extended by the current study as we found that the regulatory role of EP4 receptors translates to preventing the interaction of eosinophils with the endothelium, which is probably the most crucial step in eosinophil recruitment to the sites of inflammation.…”
Section: Discussionsupporting
confidence: 65%
“…This effect was at least partially reversed by the EP4 antagonist [18], although EP2 receptors were also found to be involved in this setup. In further experiments, we could substantiate the inhibitory role of EP4 receptors in eosinophils in assays of CD11b upregulation, production of reactive oxygen species and Ca 21 mobilization [40]. These findings have now fundamentally been extended by the current study as we found that the regulatory role of EP4 receptors translates to preventing the interaction of eosinophils with the endothelium, which is probably the most crucial step in eosinophil recruitment to the sites of inflammation.…”
Section: Discussionsupporting
confidence: 65%
“…EP4 may inhibit migration and adhesion of eosinophils (Table 3). In human eosinophils, EP4 mRNA was highly expressed (Mita et al, 2002;Luschnig-Schratl et al, 2011). The selective EP4 agonist ONO-AE1-329 potently attenuated the chemotaxis of human peripheral blood eosinophils through the PI3K pathway, but not the cAMP pathway (LuschnigSchratl et al, 2011).…”
Section: Other Immune Cellsmentioning
confidence: 99%
“…Respiratory burst of leukocytes was quantified by oxidation of nonfluorescent 29-79-dichlorodihydrofluorescein to fluorescent 29-79-dichlorofluorescein in flow cytometry (18).…”
Section: Respiratory Burstmentioning
confidence: 99%